Aspek Hukum Penggunaan Surat Berharga Pada Dunia Perbankan Bagi Masyarakat Indonesia - Roziana, Refsi roziana; Efendi, Fithria habib efendi; Ameilia, Deva; Herlika, Eren; Utami, Aisyah putri (Jurnal Kewirausahaan & Inovasi, 2023)
Indonesia's economic activities, Indonesia's economic development is inseparable from the role of the banking world, which is the main driving force for the national economy. The world of banking acts as an intermediary for the real sector and the financial sector in people's economic activities. In its activities, banking collects and distributes funds from the public and then returns them to the community in the form of credit or money loans. Indeed, in the context of banking life, both customers depositing funds and customers receiving funds are equally important. Because it is from both sides of the customer that the bank can run its business. From customers depositing bank funds, they will receive business capital, which then from customers receiving funds, the funds are channeled by obtaining profits in the form of interest. It can be said that the bank's business is to take advantage of the difference between the interest on savings/deposits, and the interest on the loans it distributes. Thus it can be said that the existence of customers is the "heart" of banking life, without customers a bank will not exist and will have no meaning in society. The bank will grow if the customer makes it big, otherwise the bank will collapse if the customer no longer trusts it. In its operational activities, the bank has securities instruments. In addition to securities as letters of legitimacy, there are other documents of legitimacy, such as bike deposit tickets, goods deposit certificates (hat deposit) and so on. One of the instruments that play a large role in banking activities is the existence of securities in the form of checks, current accounts, certificates of deposit, and time deposits. These securities have a cash value equal to the value stated on the securities. For holders of securities (appointment and replacement letters) this letter is the only letter of legitimacy for them. If he loses the letter, then he can no longer ask for the fulfillment of his rights to the debtor, except in matters regulated by law. Thus, we see the difference between letters on appointment and on replacement as letters of legitimacy compared to other letters as letters of legitimacy. Based on this description, it can be seen that the important role of securities for the banking world and for society in general is that the writer is very interested in conducting research with that title.